Pengaruh Korupsi dan Variabel Makroekonomi Terhadap Pembangunan Manusia : Studi Kasus ASEAN - Annisa Aulia Fitriani; Ariusni (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of corruption and macroeconomic variables on human development in ASEAN. This study uses macro data sourced from Transparency International, World Bank, and Human Development Report (United Nations Development Programme). This study analyzes 9 countries in ASEAN from 2006 to 2023. This study uses a quantitative research design using the Panel Data analysis method with E-Views 12 software. The results of this analysis show that the corruption perception index is positive and significant to the human development index. Government spending is positive and significant to the human development index. Gross domestic product is positive and significant to the human development index. Foreign direct investment is positive and insignificant to the human development index.This study shows the effect of corruption and macroeconomic variables on human development in ASEAN. This research is expected to be the basis of policy planning for related institutions in order to improve human development in ASEAN.